Global Change and Forest Disturbances in the Mediterranean Basin: Breakthroughs, Knowledge Gaps, and Recommendations - Peñuelas, Josep; Sardans, Jordi (Forests, 2021)
Forest ecosystems in the Mediterranean Basin are mostly situated in the north of the Basin (mesic). In the most southern and dry areas, the forest can only exist where topography and/or altitude favor a sufficient availability of water to sustain forest biomass. We have conducted a thorough review of recent literature (2000–2021) that clearly indicates large direct and indirect impacts of increasing drought conditions on the forests of the Mediterranean Basin, their changes in surface and distribution areas, and the main impacts they have suffered. We have focused on the main trends that emerge from the current literature and have highlighted the main threatens and management solution for the maintenance of these forests. The results clearly indicate large direct and indirect impacts of increasing drought conditions on the forests of the Mediterranean Basin. These increasing drought conditions together with over-exploitation, pest expansion, fire and soil degradation, are synergistically driving to forest regression and dieback in several areas of this Mediterranean Basin. These environmental changes have triggered responses in tree morphology, physiology, growth, reproduction, and mortality. We identified at least seven causes of the changes in the last three decades that have led to the current situation and that can provide clues for projecting the future of these forests: (i) The direct effect of increased aridity due to more frequent and prolonged droughts, which has driven Mediterranean forest communities to the limit of their capacity to respond to drought and escape to wetter sites, (ii) the indirect effects of drought, mainly by the spread of pests and fires, (iii) the direct and indirect effects of anthropogenic activity associated with general environmental degradation, including soil degradation and the impacts of fire, species invasion and pollution, (iv) human pressure and intense management of water resources, (v) agricultural land abandonment in the northern Mediterranean Basin without adequate management of new forests, (vi) very high pressure on forested areas of northern Africa coupled with the demographic enhancement, the expansion of crops and higher livestock pressure, and the more intense and overexploitation of water resources uses on the remaining forested areas, and (vii) scarcity and inequality of human management and policies, depending on the national and/or regional governments and agencies, being unable to counteract the previous changes. We identified appropriate measures of management intervention, using the most adequate techniques and processes to counteract these impacts and thus to conserve the health, service capacity, and biodiversity of Mediterranean forests. Future policies should, moreover, promote research to improve our knowledge of the mechanisms of, and the effects on, nutrient and carbon plant-soil status concurrent with the impacts of aridity and leaching due to the effects of current changes. Finally, we acknowledge the difficulty to obtain an accurate quantification of the impacts of increasing aridity rise that warrants an urgent investment in more focused research to further develop future tools in order to counteract the negative effects of climate change on Mediterranean forests.